The year in tech, 2021 : the insights you need from Harvard Business Review. (Insights you need from Harvard Business Review., 2021)
"A year of HBR's essential thinking on tech--all in one place. From the latest applications of AI to blockchain-enabled business models to 5G networks, the most important technological innovations of the past year are reshaping the present and future of business. What should you and your company be doing now to take advantage of the new opportunities they are creating? The Year in Tech, 2021: The Insights You Need from Harvard Business Review will help you understand today's most essential thinking on these topics, what the latest tech innovations mean for your organization, and how you can use them to compete and win in the new landscape of business."--